2020
DOI: 10.1159/000506902
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy of Parasellar Tumours

Abstract: Parasellar tumours represent a wide group of intracranial lesions, both benign and malignant. They may arise from several structures located within the parasellar area or they may infiltrate or metastasize this region. The treatment of the tumours located in these areas is challenging because of their complex anatomical location and their heterogenous histology. It often requires a multimodal approach, including surgery, radiation therapy (RT), and medical therapy. Due to the proximity of critical structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 133 publications
(186 reference statements)
0
13
0
Order By: Relevance
“…The studies reported the highest marginal dose were, in fact, those associated with the best tumor control rate and PFS over time. Due to the basal anatomical location of these tumors and their close proximity/contact to the optic system, dose reduction to decrease the risk of new or further optic neuropathy may be necessary [ 7 ]. Losa et al suggested that hypofractionated GK is a safe and effective treatment allowing to prescribe high radiation dose to the tumor minimizing the risk of radiation-induced optic injury as well (see 4.4 Multisession Gamma Knife radiosurgery for pituitary tumors) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies reported the highest marginal dose were, in fact, those associated with the best tumor control rate and PFS over time. Due to the basal anatomical location of these tumors and their close proximity/contact to the optic system, dose reduction to decrease the risk of new or further optic neuropathy may be necessary [ 7 ]. Losa et al suggested that hypofractionated GK is a safe and effective treatment allowing to prescribe high radiation dose to the tumor minimizing the risk of radiation-induced optic injury as well (see 4.4 Multisession Gamma Knife radiosurgery for pituitary tumors) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…GK allows to precisely deliver high doses of radiation to small targets minimizing the volume of normal brain structures irradiated to high doses, such as the optic pathway; it is thus frequently employed in patients with pituitary tumors. GK is usually given in single fraction or, less frequently, in a reduced number of fractions (from 2 to a maximum of 5) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, side effects of irradiation are delayed and may include hypothalamic complications ( 9 ). Among modern techniques, proton therapy may take an increasing place in the treatment of residual or recurrent CP because of the dosimetric characteristics of protons and limited off-target toxicity ( 2 , 85 ).…”
Section: Prevention and Treatment Of Sleep Disorders In Patients With...mentioning
confidence: 99%
“…They include conventional external radiotherapy, proton beam therapy, stereotactic radiotherapy, and radiosurgery. Usually, these modalities are used in combination with partial surgery, or more rarely alone [ 21 , 22 ]. When combined with surgery, radiation techniques can be employed in two different settings: immediately after an incomplete surgery (partial surgery decided by the surgeon), or after surgery, during the follow-up of the patient, when a new tumor remnant appears, or if a previously known tumor remnant becomes progressive (radiotherapy as a second step).…”
Section: Management Of Craniopharyngiomas: a Multimodal Approachmentioning
confidence: 99%